PENDIDIKAN BERBASIS MASYARAKAT DI PONDOK PESANTREN - Nurhattati Fuad (Universitas Negeri Jakarta, 2012)
This research tries to elaborate and analyse the dynamic growth of pondok pesantren (pontren) Al Ittifaq, Bandung West Java as a religiously-based educational institution. In a detail, the research elaborates